Pertanggungjawaban Pelaku Usaha Yang Tidak Menyediakan Jaminan Garansi Dalam Transaksi Jual Beli Handphone Dalam Perspektif Perlindungan Konsumen - Ambodo, Angga Dwi; Supriyono (CV. Kurnia Grup, 2024)
This study discusses the accountability of business actors who do not provide warranty guarantees in mobile phone buying and selling transactions from the perspective of consumer protection. In the rapidly developing digital and technological era, mobile phones are one of the basic needs for society. However, there are still business actors who do not provide warranty guarantees for the products they sell, which ultimately harms consumers. This study aims to analyze the legal protection provided to consumers and the responsibilities of business actors in this case. The research method used is a normative juridical approach by examining various relevant laws and regulations and related case studies. The results of the study show that consumer protection of the responsibility of business actors' products to consumers in mobile phone buying and selling transactions is not in accordance with the provisions of Law Number 8 of 1999 concerning Consumer Protection. Business actors do not pay attention to the responsibility of their products related to after-sales service, many business actors ignore their obligations to fulfill warranty guarantees, so that here consumers feel very disadvantaged. The responsibility of business actors if the goods are damaged during the warranty period must repair or replace the damaged product with new goods and return it to the consumer in good condition and free of charge and the business actor must guarantee for the rest of the product's warranty. In the principle of product liability or product liability, the system of absolute responsibility and presumption of negligence liability with reverse proof applies, consumers who feel harmed by the product for defective or unsafe goods can fulfill compensation without having to blame the existence or absence of elements of fault on the part of business actors. The responsibility of business actors who do not provide a guarantee in buying and selling mobile phones has not gone well, often business actors are not willing to give their responsibilities to consumers who do not have a guarantee guarantee, even though the business actors themselves trade the goods without a guarantee guarantee.